2017
DOI: 10.1523/jneurosci.0560-17.2017
|View full text |Cite
|
Sign up to set email alerts
|

Changes in White Matter Microstructure Impact Cognition by Disrupting the Ability of Neural Assemblies to Synchronize

Abstract: Cognition is compromised by white matter (WM) injury but the neurophysiological alterations linking them remain unclear. We hypothesized that reduced neural synchronization caused by disruption of neural signal propagation is involved. To test this, we evaluated group differences in: diffusion tensor WM microstructure measures within the optic radiations, primary visual area (V1), and cuneus; neural phase synchrony to a visual attention cue during visual-motor task; and reaction time to a response cue during t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
47
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 48 publications
(49 citation statements)
references
References 54 publications
(28 reference statements)
2
47
0
Order By: Relevance
“…Our current experimental and computational findings, as well as past work (Bells et al, ), show a fundamental connection between white matter microstructure and neural synchronization that appears critical for cognitive processing. Although studies comparing patients and healthy cohorts are essential in delineating such a connection, our patient based cross‐sectional studies ultimately do not provide evidence of the role of myelin plasticity in neural communication and cognition.…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations
“…Our current experimental and computational findings, as well as past work (Bells et al, ), show a fundamental connection between white matter microstructure and neural synchronization that appears critical for cognitive processing. Although studies comparing patients and healthy cohorts are essential in delineating such a connection, our patient based cross‐sectional studies ultimately do not provide evidence of the role of myelin plasticity in neural communication and cognition.…”
Section: Discussionsupporting
confidence: 79%
“…Damage to myelin and axons alters conduction velocities and decreases temporal synchrony within neural ensembles by increasing the variance in conduction velocity, resulting in impaired neural function (Bells et al, ; Fields, ; Nunez et al, ; Pajevic et al, ). In past DTI work, decreased FA in pediatric MS patients was associated with increased connectivity within the resting state visual network (Akbar et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Specifically, we have shown that children treated for PBT display abnormal neural activation compared to typically developing children that predicts impaired cognitive function (Dockstader et al, ; Dockstader, Wang, Bouffet, & Mabbott, ). Indeed white matter injury may have its impact on cognition via influence on neural communication (Bells et al, ). Consequently, the cognitive deficits observed in PBT survivors may result from tumor and treatment‐related changes in neural synchrony between different brain regions.…”
Section: Introductionmentioning
confidence: 99%